2006
DOI: 10.1103/physrevd.74.022002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the mechanical loss of a cooled reflective coating for gravitational wave detection

Abstract: We have measured the mechanical loss of a dielectric multilayer reflective coating (ion-beam sputtered SiO2 and Ta2O5) in cooled mirrors. The loss was nearly independent of the temperature (4 K ∼ 300 K), frequency, optical loss, and stress caused by the coating, and the details of the manufacturing processes. The loss angle was (4 ∼ 6) × 10 −4 . The temperature independence of this loss implies that the amplitude of the coating thermal noise, which is a severe limit in any precise measurement, is proportional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…The appearance of slip lines requires that the native Ta oxide film supposes no barrier for dislocations and fails via shear at slip edges [42]. Consistent with our observation, the 1-nm-thick native Ta oxide film is not expected to be a barrier for dislocations due to its thinness and the fact that the Young's modulus of Ta oxide (140 GPa) [43] is lower than that of Ta(189 GPa).…”
Section: B Atomic Force Microscopysupporting
confidence: 86%
“…The appearance of slip lines requires that the native Ta oxide film supposes no barrier for dislocations and fails via shear at slip edges [42]. Consistent with our observation, the 1-nm-thick native Ta oxide film is not expected to be a barrier for dislocations due to its thinness and the fact that the Young's modulus of Ta oxide (140 GPa) [43] is lower than that of Ta(189 GPa).…”
Section: B Atomic Force Microscopysupporting
confidence: 86%
“…It has been applied for data at room temperature [21,22], as well as at low temperatures [23][24][25]. In these experiments, dependence of the mechanical loss of the dielectric coating with frequency has sometimes been considered [21], but, anyway, the frequency range of interest never goes above a few kilohertz in those applications.…”
Section: Discussionmentioning
confidence: 99%
“…For isotropic materials with a Poisson's ratio much lower than unity, it can be shown that the ratio between the energies can be simplified reduced to 3tcYc tsYs , where Y i denote the Young's modulus of element i, and t i its thickness [23,31]. Quartz is only slightly anisotropic, so this simplified model remains relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations